1977
DOI: 10.1128/jvi.22.3.816-821.1977
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Epstein-Barr virus receptors, but absence of virus penetration, in cells of an Epstein-Barr virus genome-negative human lymphoblastoid T line (Molt 4)

Abstract: This paper reports a unique type of interaction of Epstein-Barr virus (EBV) with an EBV receptor-positive, genome-negative human lymphoid T cell line (Molt 4), which can be summarized as follows. Although Molt 4 cells express receptors for EBV, they appear to block the penetration of this virus. These observations are derived from combined studies with immunofluorescence and electron microscopy. It is possible that T cell lines bearing receptors for EBV may express such a control on virus penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…However, earlier studies showed that T-acute lymphoblastic leukemia (ALL) cell line (MOLT4), null cells, and undifferentiated T-cells also expressed functional C3d-receptors and are able to bind to EBV. 42,43 In addition, Tatsumi et al . 44 detected expression of CD21, which corresponds to the C3d component of EBV receptor, in 80% (8/10) of thymic stage T-cell ALL/lymphoblastic lymphoma (LBL), but not in pro-or early thymic T-ALL/ LBL.…”
Section: Site Of Presentationmentioning
confidence: 99%
“…However, earlier studies showed that T-acute lymphoblastic leukemia (ALL) cell line (MOLT4), null cells, and undifferentiated T-cells also expressed functional C3d-receptors and are able to bind to EBV. 42,43 In addition, Tatsumi et al . 44 detected expression of CD21, which corresponds to the C3d component of EBV receptor, in 80% (8/10) of thymic stage T-cell ALL/lymphoblastic lymphoma (LBL), but not in pro-or early thymic T-ALL/ LBL.…”
Section: Site Of Presentationmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) infects only B lymphocytes of human and certain non-human primate origin and derived lines. This sharp host cell restriction is probably determined at the receptor level since functional EBV-receptors have only been found on B-cell-derived lines 1979b;Menezes et al, 19776). The receptor control of EBV infection was recently confirmed by the successful artificial introduction of EBV into previously noninfectable, EBV-receptor negative human, simian, and murine targets (Graessman et al, 1980;Volsky et al, 1980).…”
mentioning
confidence: 99%
“…CEM cells lack a receptor for EBV, and can neither bind nor be infected by the virus. MOLT-4 cells have receptors for EBV but cannot internalize or be infected by the virus (Menezes et al, 1977). Slight depolarization was observed upon addition of EBV to CEM cells but to an extent similar to that of control treated cells.…”
Section: Resultsmentioning
confidence: 86%
“…Only one non-B cell line has been shown to possess receptors for EBV. MOLT-4, a T cell line, binds both EVB and C3b but the virus is not internalized and infection does not occur (Menezes et al, 1977). We report here detection of rapid changes in membrane potential following EBV binding to receptor bearing cells; the observed changes difl'er in time course and direction with respect to the cell's capacity to internalize the virus and the cell type.…”
mentioning
confidence: 72%
See 1 more Smart Citation